Crystal structure, infrared spectra and microwave dielectric properties of new ultra low-loss Li6Mg7Ti3O16 ceramics. Issue 16 (November 2017) - Pan, H.L.; Wu, H.T.
Abstract: New ultra low-loss Li6 Mg7 Ti3 O16 (LMT) ceramics were prepared via the conventional solid-state reaction method. The crystal structure, sintering characteristics, infrared spectrum and microwave dielectric properties were studied. Rietveld refinement was performed to research the crystal structure and the lattice parameters were obtained. The microwave dielectric properties of the sintered samples exhibited the close relationship with the sintering characteristics. The bond energy of the LMT ceramics was calculated to analyze the intrinsic factors. The major polarization contribution was mainly dependent on the absorption of phonon oscillation. The ceramics sintered at 1550 °C exhibited the excellent properties of ε r = 15.27, Q·ƒ = 209, 400 GHz and τ f = − 11.32 ppm/°C.